Transformasi Kurikulum Merdeka Belajar di Madrasah Berbasis Pesantren - Rachman, Lutfi; Muallif, Muallif (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Education is an essential factor determining the progress of a nation, and an effective curriculum is necessary to produce quality generations. In this context, pesantren as traditional educational institutions play a crucial role in integrating religious education and general education, particularly through the implementation of the Merdeka Learning curriculum. This study aims to explore how the implementation of the Merdeka Learning curriculum in pesantren can build the character and competencies of students to face global challenges. The research method used is qualitative with a library research approach, involving the analysis of various literature related to the Merdeka Learning curriculum and education in pesantren. The results of the study indicate that the Merdeka Learning curriculum in pesantren focuses not only on academic aspects but also on the development of soft skills and noble values, employing interactive and practical teaching methods. The contribution of this research is to provide new insights into the development of a holistic and relevant curriculum in pesantren, as well as to suggest strategic steps to enhance the quality of education in pesantren and other educational institutions in Indonesia. Thus, this study is expected to encourage a stronger integration between religious education and practical skills in pesantren curricula to produce a generation that is ready to make positive contributions to society.